THE IMPORTANCE OF MOLECULAR GENETICS FOR CANCER SCREENING - Jekic, Biljana (HEALTH CARE, 2020)
Despite the advance of medicine, cancer remains among the leading causes of deaths worldwide. The main reason is the progression of the disease without the symptoms until the untreatable stages are achieved. To prevent this, the development of new, more sensitive and specific screening methods for early detection of cancer is necessary. Molecular genetics, through the improvement of existing and development of new methods and analysis cost reduction, could provide tools for the achievement of this goal. There are essential differences in approach regarding the purpose of screening methods: screening for hereditary cancer syndromes or sporadic cancers. In the case of hereditary cancer syndromes, molecular genetics methods are used to search for germline mutations in defined genes, to establish a final diagnosis or to estimate the risk of cancer for the patient that is identified as a member of a family in risk. The mutation is present in all cells of the organism and can be detected through non-invasive analysis of DNA from body fluids or the buccal swab. Development of molecular genetics method for screening for sporadic cancers in a healthy population, without any knowledge of cancer location or genetic change, could rely on the search of tumor genetic material in body liquids (liquid biopsies). In this case, the search for change in circulating cell-free DNA (cfDNA) concentration or genetic and epigenetic changes in circulating tumor DNA (ctDNA) in a blood sample could reveal development of a tumour. Additionally, epigenetic changes should also be considered in screening for cancers.
Keywords: molecular genetics method, screening methods, hereditary cancer syndromes, sporadic cancers